Narodowy fundusz ochrony środowiska i gospodarki wodnej jako podmiot udzielający pomocy publicznej - Bartniczak, Bartosz (National fund for environmental protection and water management as an institution granting state aid, 2006)
In Poland since 2000 has been in force the Act on Conditions for Approving and Supervising Public Support for Entrepreneurs. One of the area’s, where stale aid is admitted is environmental protection. And one of the main subjects, which can grant slate aid in this area is the National Fund for Environmental Protection and Water Management. The aim of this article is to show the role of the National Fund in this area, and make analysis of granted state aid.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 13-24